Batik SMEs Efficiency and Entrepreneurship Role in Innovation - Kurniati, Edy Dwi; Prajanti, Sucihatiningsih Dian Wisika (Universitas Negeri Semarang, 2018)
In the long term, batik SMEs to compete in the local and global markets can not only rely on production capabilities rooted in local sources of uniqueness, but must have efficiency of economies scale for resource access and innovation. In a competitive environment, entrepreneurs in the batik industry have an important role to improve the efficiency. This study analyzed the role of entrepreneurs in the economic efficiency. This study applies production model to describe the entrepreneurs role on economic efficiency. The study was conducted by interviews to 100 Batik SMEs managers-owners in the Batik Centre in Solo, Pekalongan and Rembang. The entrepreneurs role in innovation in term of product innovation, marketing innovation, and business alliances (cooperatives). Data analysis was performed using Stochastic Frontier and Deterministic Regression Analysis. The empirical results of the technical inefficiency effects model suggest that the entrepreneurs role in product innovation, marketing innovation and business alliances are important factors affecting economic efficiency of batik SMEs. The role of entrepreneurship in marketing innovation has the highest elasticity of the production and sales of batik, and then followed by the role of entrepreneurs in new product innovation and business alliances.